Initial responses to COVID-19 by four Central American governments (2021)
The article reviews the initial responses to the Covid-19 pandemic of Guatemala, El Salvador, Costa Rica, and Panama. Using official documents, the characteristics of the responses that these governments execute during the first semester of 2020 are identified and compared. It is concluded that, although governments mainly develop biosafety measures, there are differences in the strategies adopted, possibly motivated by the prevailing social, political, and economic characteristics in those countries. The governments of these countries seem to be influenced to follow the recommendations issued by international organizations by the lack of information about the COVID-19 pandemic, without interest to review these measures according to the characteristics of their countries.